Randomised study of the influence of non-steroidal anti-inflammatory drugs on the treatment of peptic ulcer in patients with rheumatic disease. Issue 2 (February 1987) - Manniche, C; Malchow-Møller, A; Andersen, J R; Pedersen, C; Hansen, T M; Jess, P; Helleberg, L; Rasmussen, S N; Tage-Jensen, U; Nielsen, S E
Abstract : Sixty-seven patients with rheumatic disease, treated with non-steroidal anti-inflammatory drugs (NSAIDs), entered a controlled trial with a diagnosis of duodenal (n = 51), gastric (n = 14), or gastric and duodenal (n = 2) ulcers. The main objectives of the study were a comparison of ranitidine and sucralfate in ulcer treatment, and to observe the influence of continued NSAID administration during peptic ulcer therapy. Ulcers healed within nine weeks in 52 patients. The mean healing time was similar in 27 patients given ranitidine 150 mg bd (4.9 weeks) and 25 patients given sucralfate 1 g qid (4.6 weeks). In patients with unhealed ulcers after nine weeks of treatment, healing was obtained in seven after further therapy for 3-9 weeks. Of the 30 patients who continued NSAIDs during treatment with either ranitidine or sucralfate, 23 ulcers healed (mean healing time: 5.0 weeks). Of 32 patients in whom NSAIDs were stopped, ulcer healing was documented in 29 (mean healing time: 4.6 weeks). The difference in healing rates was not statistically significant (p greater than 0.10). The outcome of ulcer treatment did not differ in patients with rheumatoid arthritis and patients suffering from osteoarthritis. During a 12 month follow up 14 symptomatic ulcer recurrences were recorded.